1977
DOI: 10.1007/bf01035993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glycerol nonutilizing and protoperithecial mutants ofNeurospora

Abstract: Mutants defective in polyol metabolism and/or in protoperithecial development were selected in Neurospora tetrasperma, a species in which protoperithecial development occurs at nonpermissively high temperature if certain polyols are used in lieu of sucrose as carbon source. Mutants selected for nonutilization of one of the four polyols tested, glycerol, mannitol, sorbitol, or xylitol, were usually found to be nonutilizers of the other three polyols as well. Mutants blocked at various stages of protoperithecial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…Moreover, the level of glycerate 3‐kinase was about twofold higher in the mutants compared with the wild type. As glycerol kinase activity is also detectable in N. crassa indicating the presence of the classical G3P pathway (Viswanath‐Reddy et al ., ), it has been suggested that the catabolic GA pathway, including the two sub‐pathways for the second part, might represent another route for glycerol catabolism in this organism. Although the GA catabolic pathway has not been described in yeasts so far, homologs of the enzyme catalyzing the first step in this pathway have been reported in S. cerevisiae (Gcy1 and Ypr1) as already mentioned above.…”
Section: Glycerol Catabolic Pathwaysmentioning
confidence: 95%
“…Moreover, the level of glycerate 3‐kinase was about twofold higher in the mutants compared with the wild type. As glycerol kinase activity is also detectable in N. crassa indicating the presence of the classical G3P pathway (Viswanath‐Reddy et al ., ), it has been suggested that the catabolic GA pathway, including the two sub‐pathways for the second part, might represent another route for glycerol catabolism in this organism. Although the GA catabolic pathway has not been described in yeasts so far, homologs of the enzyme catalyzing the first step in this pathway have been reported in S. cerevisiae (Gcy1 and Ypr1) as already mentioned above.…”
Section: Glycerol Catabolic Pathwaysmentioning
confidence: 95%
“…Currently, three glycerol metabolic pathways have been reported [24], one phosphorylative pathway [25], [26] and two oxidative pathways that are based on NAD(P) + -dependent glycerol dehydrogenases [27]. In this report, we have identified and characterized the first eukaryotic TSR and demonstrated its role in glycerol catabolism and production of glycolipids from glycerol (Figure 5, 6, S3, S4, Table 2).…”
Section: Discussionmentioning
confidence: 79%
“…Some facultative anaerobic bacteria such as Klebsiella aerogenes use the phosphorylation pathway under aerobic conditions, but can employ the oxidation pathway in the absence of oxygen (28). In some bacteria, it is also possible for glycerol to be oxidised to glyceraldehyde (29), which may then be converted to glycerate (30).…”
Section: Discussionmentioning
confidence: 99%